Reputasi Auditor sebagai Pemoderasi Pengaruh Opini Audit dan Pergantian Manajemen pada Auditor Switching - Ratna Candradewi, Nyoman; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
Auditor turnover is a behavior that the client company does to transfer the auditor . This reaserch aims to obtain empirical evidence of the effect of audit opinion and management change on auditor switching and how the auditor's reputation is able to moderate the influence of audit opinion and management change on auditor switching. Determination of the research sample using purposive sampling method with a sample of 145 companies. Data analysis techniques used are logistic regression analysis and Moderated Regression Analysis (MRA). Based on the results of this study indicate that audit opinion and management change have a significant positive effect on auditor switching. However, the auditor's reputation is unable to moderate the effect of audit opinion and management change on auditor switching. Keywords: Audit Opinion; Change of Management; Auditor Switching; Auditor’s Reputation.